Evaluation Of Government`'s Performance In Islamic Economic Perspective: Analysis Of The Indonesian State Budget And Expenditures Based On Maqashid Syariah Index - Purnamawati, Anni Muslimah (Proceedings of Annual Conference for Muslim Scholars, 2019)
This study aims to analyze the Indonesian State Budget (APBN) for fiscal years 2015 to 2019 with the maqashid shariah approach and the maqashid syariah index. Analysis of the data used is secondary data from the 2015 APBN Indonesia report until 2019. Based on the results of data exposure, it can be seen that in perspective of maqashid sharia the Indonesian State Budget in 2015-2019 has not described the level of maqashid sharia that should be. The main priority of the Indonesian State Budget is the protection of offspring (ḥifẓun-nasl), the second is protection of reason (ḥifẓul-‘aql), then the third governments focus on the protection of religion (ḥifẓud-dῑn). Fourth, the government focuses on protecting assets (ḥifẓul-māl) and finally fifth, the government provides a life protection budget (ḥifẓun-nafs), with the budget in 2019 amount of 123.1 trillion Rupiah. While on the maqashid sharia index level, the level of justice (justice) has the most budget compared to education and welfare. Based on the performance of the Indonesian State Budget, the value of maqashid sharia index in 2015 was 1.1209; in 2016 the maqashid value of the shariah index increased to 1.1719; in 2017 the value of the maqashid sharia index decreased to 1.1703; in 2018, the maqashid sharia index value will decrease to 1.0866; In 2019, the maqashid shariah index also declined to 0.9946. The average maqashid sharia index value on performance the Indonesian state budget for fiscal years 2015-2019 is 1.1088